Gameworld interfaces - Jorgensen, Kristine (The MIT Press, 2013)
Digital games tend to follow one of two trends when presenting game information to the player. The game may present game information in a naturalistic way as part of the imaginary universe presented by the game, avoiding symbolic or abstract representations that seem alien to the fictional world. Alternatively, the game may use graphical augmentations such as superimposed information, menus, and icons that points directly to important information. In 'Gameworld Interfaces', Kristine Jørgensen investigates different approaches to designing the game interface.